UJI BEBERAPA JENIS KOMPOS PADA PERTUMBUHAN BIBIT TANAMAN KARET (Hevea brasiliensis Muell Arg.) STUM MINI - Suhariyono '; Sampurno '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research was carried out at the experimental garden of Agriculture Faculty, University of Riau starting from January to April 2014 with aim to determine the effect of compost type on the growth of rubber seedlings mini stump and to determine the type of compost that gives the best effect for mini stump rubber seedlings. This research was carried out using a Randomized Design Completely (RDC), which consist of 6 treatments and 4 replications. The treatments in this research are: K1: without treatment, K2: TKKS compost 100 g/polybag(20 tonnes/ha), K3: Rice straw compost 100 g/polybag(20 tonnes/ha), K4: Water Hyacinth Compost 100 g/polybag(20 tonnes/ha), K5: Compost BJKS 100 g/polybag(20 tonnes/ha), K6: Compost Legume Cover Crop (LCC) 100 g/polybag(20 tonnes/ha). Data were analyzed statistically using Duncan's test New Multiple Range Test (DNMRT) at 5% level. Parameters measured are high accretion of shoot (cm), number of leaves (blade), increased diameter of shoot (cm), crown root ratio (g). The result of research shown, water hyacinth and BJKS compost types (100 g/polybag) effected on high increase of shoots and crown roots ratio. From some treatments, BJKS compost shown the best results are on increased number of leaves, increased diameter of shoot tunas and crown root ratio, while that at high gain the best results in the treatment plant water hyacinth compost. Keywords: mini stump, TKKS compost, rice straw compost, water hyacinth compost, BJKS compost and LCC compost.